Relevansi Prugal Living Bagi Penguatan Ketahanan Ekonomi Rumah Tangga Muslim: Perspektif Ekonomi Syariah - Kisanda Midisen; Ali Nur Ahmad; Aceng Badruzzaman; Yudianto Achmad; Tiara Purnama Smart (DPPM Universitas Pelita Bangsa, 2026)
This study aims to analyze the relevance and contribution of the concept of prugal living as a strategy to strengthen the economic resilience of Muslim households within the framework of Islamic economics. This study uses a qualitative approach through literature study and content analysis of primary Islamic texts (the Qur'an, Hadith) as well as contemporary literature on prugal living. The analysis shows that prugal living has a strong philosophical and practical alignment with the basic principles of Islamic economics, particularly iqtishad (middle stance) and the prohibition of israf and tabdzir. Operationally, prugal living contributes to the pillars of Islamic economic resilience—from proportional income management, increasing savings capacity (idkhar), to asset protection (hifzh al-mal)—while supporting the achievement of maqasid al-syariah at the household level. Prugal living is not just a lifestyle trend, but an applicable and relevant Islamic financial strategy to build the economic resilience of Muslim households through resource optimization, value prioritization, and immunity from consumerism.